THE ROLE OF MICRO-CREDENTIALS AND SKILL-BASED RECRUITMENT IN INDONESIA’S BEAUTY VOCATIONAL EDUCATION - Ursila Indah Pratiwi; Sri Usodoningtyas; Sofi Nur Takhiyah; Octania Hartanto; Dayinta Alkencono Jati (Adornata : Ethnobeauty and Wellness Journal, 2025)
The transformation of vocational education in the digital economy era demands a paradigm shift from diploma-based recognition toward a competency-based system. This study aims to analyze the role of micro-credentials and skill-based hiring practices in enhancing the employability skills of graduates from beauty vocational schools Vocational High School in Indonesia. A mixed-methods approach with a sequential explanatory design was employed. Quantitative data were collected from 212 graduates of beauty Vocational High School across East Java, West Java, and Yogyakarta through an online survey, while qualitative data were obtained via in-depth interviews with 12 salon owners, 5 HR managers from the cosmetics industry, and 8 beauty vocational teachers. The results indicate that specific micro-credentialssuch as bridal make-up, nail art, and digital beauty marketing certificates have a significant positive effect on graduates’ employability levels (β = 0.47; p < 0.001). Interviews confirmed that the industry values verified competencies and skill portfolios more highly than formal diplomas. This study underscores the urgency of integrating micro-credentials into Vocational High School curricula to strengthen the alignment between education and the needs of the modern beauty industry.